Integrating human behavior dynamics into drought risk assessment—A sociohydrologic, agent‐based approach. (22nd April 2019) - Wens, Marthe; Johnson, J. Michael; Zagaria, Cecilia; Veldkamp, Ted I. E.
Abstract : Droughts are a persistent and costly hazard impacting human and environmental systems. As climate variability continues to increase and socioeconomic development influences the distribution of wealth and people, drought risk is expected to increase in many parts of the world. The unique characteristics of droughts—namely their slow onset, large spatiotemporal extent, human‐influenced propagation, delayed impacts and teleconnection potential—make it difficult to correctly assess drought impact and calculate risk. Further complicating this calculation is the capacity for humans to make adaptive decisions before, during, and after a drought event, which in turn alters expected impacts. In this sense, droughts are equally a social and hydroclimatic issue. Risk perception is one of the main factors driving adaptation decisions, yet most models neglect how humans view and respond to risk, and in particular how experiences influence decisions through time. In this overview, we describe a framework that extends the traditional risk modeling approach to include the two‐way feedback between the transient adaptation decisions and drought exposure, vulnerability and hazard. We discuss how a sociohydrologic, agent‐based modeling setup, focused on individual and collective actions, can simulate the adaptive behaviors of different stakeholders to examine how emergent actions might influence projected drought risk. We suggest such an approach can provide a test‐bed for understanding adaptive behaviors in an increasingly drought‐prone world and could allow for better prioritization of drought adaptation strategies; refined understanding of future scenarios; and a vehicle to drive planning and resilience building. This article is categorized under: Science of Water > Water Extremes Engineering Water > Planning Water Engineering Water > Methods Abstract : Combining agent‐based (purple), sociohydrologic (orange), and drought risk (green) modelling techniques provides a generalized framework that can be used across a range of research questions. The intention of such a framework is to better represent individual and collective behaviors and their role in shaping drought risk projections.